2021
DOI: 10.1097/pr9.0000000000000975
|View full text |Cite
|
Sign up to set email alerts
|

Association between temporal summation and conditioned pain modulation in chronic low back pain: baseline results from 2 clinical trials

Abstract: Introduction: Temporal summation (TS) and conditioned pain modulation (CPM) represent different aspects of central pain processing. Their relationship and differential performance within distinct body locations are not well understood. Objectives: To examine the association between TS and CPM in chronic low back pain and the influence of testing location on this relationship. Methods: We analyzed baseline data from 2 clinical trials on participants with chronic low back pain (n 5 264; 47.3% female; mean age 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…37 Dysfunctional CPM is previously identified in chronic NNP 10 and chronic pain in general. 38 The presence of increased TS and impaired CPM, which are commonly associated, 39 is highly suggestive of altered central pain processing early in NNP. Recent research has identified correlations between PPT and TS in chronic widespread musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%
“…37 Dysfunctional CPM is previously identified in chronic NNP 10 and chronic pain in general. 38 The presence of increased TS and impaired CPM, which are commonly associated, 39 is highly suggestive of altered central pain processing early in NNP. Recent research has identified correlations between PPT and TS in chronic widespread musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Two measurements will be conducted twice bilaterally. Each measure will be assessed in the middle side between L1-L5, 5 cm apart from the lumbar spinal processes [7,[42][43][44].…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
“…It is a 20-item self-administered questionnaire which patients are asked to indicate the score from 0 to 3 that best indicates how they feel at the time they are lling in the questionnaire. The range of score is 20-80: no anxiety (≤ 20), mild (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), moderate (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and severe anxiety (60-80).…”
Section: Quality Of Life and Mental Healthmentioning
confidence: 99%
“…CPM is suggested to test the integrity of DNIC mechanisms only, so is unlikely to be informative of alterations in other descending control systems, such as those involved in stress-induced analgesia [11 ▪▪ ]. Other psychophysical tests, including quantitative sensory testing (QST) offset analgesia or temporal summation of pain [18][19][20][21] offer varying levels of sensitivity to detect pathology in different pain phenotypes, but they are similarly unlikely to be sufficient in isolation, nor are they expressly intended to probe descending control mechanisms. Multimodal convergent operations approaches to understanding complex behaviour are not new [22] and recent reports indicate their potential in pain research.…”
Section: Endogenous Pain Control and Novel Avenues For Pharmacotherapymentioning
confidence: 99%